Leveraging Private Sector Finance for Rural Piped Water Infrastructure in Kenya : The Use of Output-Based Aid - Virjee, Kameel (World Bank, Washington, DC, 2012)
An innovative approach to rural infrastructure finance in Kenya is facilitating access to finance for community-based water providers by blending output-based subsidies and commercial finance. The project is being implemented by K-Rep Bank, a local commercial bank specialized in microfinance lending, with support from the Water and Sanitation Program, the global partnership on output-based aid, and the European Union's water facility. The project, which began with 21 sub-projects, is in the process of expanding to a national scale and will target over 165,000 beneficiaries in 55 communities. The initial experience indicates that innovation in access to infrastructure finance is possible in Kenya's rural water sector and that, inter alia, output-based subsidies can be useful in addressing affordability constraints for community-based water providers.